2020
DOI: 10.1109/jeds.2020.3021031
|View full text |Cite
|
Sign up to set email alerts
|

Compact Modeling of Multi-Layered MoS2 FETs Including Negative Capacitance Effect

Abstract: In this paper, we present a channel thickness dependent analytical model for MoS2 symmetric double-gate FETs including negative capacitance (NC) effect. In the model development, first thickness dependent model of the baseline 2D FET is developed, and later NC effect is included in the model using the Landau-Khalatnikov (L-K) relation. To validate baseline model behavior, density functional theory (DFT) calculations are taken into account to obtain numerical data for the K and Λ valley dependent effective mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…This model accounts for the non-idealities of the channel material and considers the impact of Schottky contact. In addition, Nandan et al [ 15 ] proposed a double gate MoS 2 FET which considered the effect of channel thickness. Additionally, Khare et al [ 16 ] reported that the threshold voltage of MoS 2 FET is influenced by the layer’s thickness.…”
Section: Introductionmentioning
confidence: 99%
“…This model accounts for the non-idealities of the channel material and considers the impact of Schottky contact. In addition, Nandan et al [ 15 ] proposed a double gate MoS 2 FET which considered the effect of channel thickness. Additionally, Khare et al [ 16 ] reported that the threshold voltage of MoS 2 FET is influenced by the layer’s thickness.…”
Section: Introductionmentioning
confidence: 99%
“…ML-MoSi 2 N 4 is an indirect band gap semiconductor with the experimental band gap value of 1.94 eV. Its elastic constant is ∼ 4 times of ML-MoS 2 , and the carrier mobilities in it are ∼ 4 times and ∼ 4-6 times of ML-MoS 2 (the most widely studied 2D material for FETs application [8], [16]- [28]). Its lattice thermal conductivities [11], [12] are approximately 1.6 times silicon (Si) and much higher than other widely known 2D semiconductors [29]- [31] (ML-MoS 2 , As, Sb, silicene and, ML-BP), but much lower than graphene [29], [32].…”
Section: Introductionmentioning
confidence: 99%